Structural, Electronic and Optical Properties of Cubic Perovskite CsPbX3 (X= Br, Cl and I) - Abdulkareem, Nawzad A.; Sami, Sarkawt A.; Elias, Badal H. (Science Journal of University of Zakho, 2020)
Plane waves with norm conserving pseudopotentials (PW-PP) method in conjunction with density functional theory (DFT) frame work have been used to investigate structural, electronic and optical properties of lead-halide cubic perovskite CsPbX3 (X=Br, Cl and I). The generalized gradient approximation (GGA), specifically Perdew-Burke-Ernzerhof (PBE) flavor, has been chosen to treat the exchange correlation term of Kohn-Sham equation. Structural parameters are comparable with other theoretical and experimental studies. In spite of good agreement of our band gap values  with other theoretical works, however, they were not comparable when compared to the experimental  values due to the well-known problem of Eg value underestimation of DFT. To update the  value, we have used GW method as a self-consistent quasiparticle method on energies and wave functions and indeed they have been improved. Optical properties have been calculated using density functional perturbation theory (DFPT). Our results show that CsPbX3 (X=Br, Cl, I) has maximum response to the electromagnetic spectrum at low energies (visible region) but minimum response at high energies.
Keywords: Ab initio calculation; Structural; electrical and optical properties; Band gap; Perovskites CsPbX3